Pronounced surface enrichment of fluorinated ionic liquids in binary mixtures with methoxy-functionalized ionic liquids - Heller, Bettina; Paap, Ulrike; Maier, Florian; Steinrück, Hans-Peter (Journal of Molecular Liquids, 2020)
Different binary mixtures of two functionalized ionic liquids (ILs), namely 1,3-di(methoxy)imidazolium hexafluorophosphate, [(MeO)2Im][PF6], and 3-methyl-1-(3,3,4,4,4-pentafluorobutyl)imidazolium hexafluorophosphate, [PFBMIm][PF6], are investigated in the liquid state by angle-resolved X-ray photoelectron spectroscopy (ARXPS). Both ILs consist of the same [PF6]− anion but differ in the functionalization of the cation: [(MeO)2Im][PF6] has an oxygen atom directly bound to each nitrogen atom of the imidazolium ring whereas in [PFBMIm][PF6] the two terminal carbon atoms of the butyl chain are fully fluorinated. Due to different electronic structures of the cations of both ILs, the ARXP signals of the two cations and of the anion can be well distinguished, which allows to identify preferential chain orientation as well as enrichment and depletion effects at the surface. In the mixtures with 50, 90 and 95 mol% [(MeO)2Im][PF6], a very pronounced enrichment of the [PFBMIm]+ cation at the IL/vacuum interface is observed. The fluorinated chain points towards the vacuum side and thereby attenuates the signal of the [PF6]− anion. Decreasing the temperature from 95 °C to close to the solidification temperatures of the mixtures leads to a more pronounced surface enrichment of the [PFBMIm]+ cation and of the fluorinated chain.
CRIS-Team Scopus Importer:2020-03-17
Keywords: Ionic liquid; Mixture; Surface enrichment; X-ray photoelectron spectroscopy